Relationships between HBeAg status of patients with chronic hepatitis B and changes in serum TNF-α, viral load and severity of morphological changes in the liver according to non-invasive tests - A. B. Khelemendyk; O. V. Riabokon; Yu. Yu. Riabokon; K. V. Kalashnyk (Zaporozhye State Medical University, 2021)
Aim - to investigate the relationship between HBeAg status of patients with chronic hepatitis B and the content of TNF-α in the serum, the level of viral load and the severity of morphological changes in the liver according to non-invasive tests. Material and methods. 70 patients with CHB were examined. Noninvasive methods were used to determine the severity of morphological changes in the liver. The content of HBV-DNA in the blood was determined by PCR, HBeAg, anti-HBe, TNF-α by ELISA. Statistical processing was performed in Statistica 13 for Windows (StatSoft Inc., No. JPZ804I382130ARCN10-J). Results. HBeAg-negative patients (78.6 %) with anti-HBe (89.1 %) predominate among patients with CHB. Lower frequency of seroconversion in patients with stages F 2-4, compared with patients with stages F 0-1 (85.7 % vs. 100 %, P < 0.05). The highest level of HBV-DNA in the blood was in HBeAg-positive patients, compared with HBeAg-negative with stages F 0-1 (P < 0.05), of whom 83.3 % of patients had HBV-DNA >20000 IU/ml (83.3 % vs. 17.7 %). Viral load in HBeAg-positive patients with activity A 0-1 was the highest (P < 0.05), namely 4 times more often HBV-DNA was >20000 IU/ml, compared with HBeAg-negative (P < 0.05) A 0-1. The content of TNF-α in the serum of patients with CHB was higher than in healthy individuals (P < 0.05). The highest content of TNF-α in the blood in HBeAg-positive patients with F 2-4, compared with HBeAg-negative with F 2-4 (P < 0.05). The severity of liver fibrosis correlated with the level of TNF-α (r = 0.31, P < 0.05). Conclusions. HBeAg-negative (78.6 %) predominate among patients with CHB. In the presence of HBeAg-positive patients F 0-1 viral load is highest (P < 0.05). HBeAg-negative patients are 2.7 times more likely (P < 0.05) to have a viral load of HBV-DNA >20000 IU/ml in the presence of A 2-3 than in A 0-1. The highest content of TNF-α is in the serum of HBeAg-positive patients with F 2-4, compared with HBeAg-negative patients and the corresponding liver fibrosis (P < 0.05).